Dietary Approach to Recurrent or Chronic Hyperkalaemia in Patients with Decreased Kidney Function - Cupisti, Adamasco (Nutrients, 2018)
Whereas the adequate intake of potassium is relatively high in healthy adults, i.e., 4.7 g per day, a dietary potassium restriction of usually less than 3 g per day is recommended in the management of patients with reduced kidney function, especially those who tend to develop hyperkalaemia including patients who are treated with angiotensin pathway modulators. Most potassium-rich foods are considered heart-healthy nutrients with high fibre, high anti-oxidant vitamins and high alkali content such as fresh fruits and vegetables; hence, the main challenge of dietary potassium management is to maintain high fibre intake and a low net fixed-acid load, because constipation and metabolic acidosis are per se major risk factors for hyperkalaemia. To achieve a careful reduction of dietary potassium load without a decrease in alkali or fibre intake, we recommend the implementation of certain pragmatic dietary interventions as follows: Improving knowledge and education about the type of foods with excess potassium (per serving or per unit of weight); identifying foods that are needed for healthy nutrition in renal patients; classification of foods based on their potassium content normalized per unit of dietary fibre; education about the use of cooking procedures (such as boiling) in order to achieve effective potassium reduction before eating; and attention to hidden sources of potassium, in particular additives in preserved foods and low-sodium salt substitutes. The present paper aims to review dietary potassium handling and gives information about practical approaches to limit potassium load in chronic kidney disease patients at risk of hyperkalaemia.